2015
DOI: 10.1021/acs.jpclett.5b00968
|View full text |Cite
|
Sign up to set email alerts
|

How Important Is the Organic Part of Lead Halide Perovskite Photovoltaic Cells? Efficient CsPbBr3 Cells

Abstract: Hybrid organic-inorganic lead halide perovskite photovoltaic cells have already surpassed 20% conversion efficiency in the few years that they have been seriously studied. However, many fundamental questions still remain unanswered as to why they are so good. One of these is "Is the organic cation really necessary to obtain high quality cells?" In this study, we show that an all-inorganic version of the lead bromide perovskite material works equally well as the organic one, in particular generating the high op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

26
820
1
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 1,023 publications
(860 citation statements)
references
References 19 publications
26
820
1
13
Order By: Relevance
“…2,[39][40][41] Contrast to the organicinorganic hybrid perovskites, purely inorganic CsPbX VII 3 perovskites exhibit excellent thermal stability. 3,38 Secondly, because the upper group-IVA elements such as Sn and Ge at the M IV site tend to be oxidized from divalent Sn 2+ /Ge 2+ to tetravalent Sn 4+ /Ge 4+ , 32,[42][43][44] and thus cause the instability issue, current halide perovskite based solar cells with high PCEs exclusively contain the toxic element -Pb. This will inevitably cause potential environmental concerns for large-scale solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…2,[39][40][41] Contrast to the organicinorganic hybrid perovskites, purely inorganic CsPbX VII 3 perovskites exhibit excellent thermal stability. 3,38 Secondly, because the upper group-IVA elements such as Sn and Ge at the M IV site tend to be oxidized from divalent Sn 2+ /Ge 2+ to tetravalent Sn 4+ /Ge 4+ , 32,[42][43][44] and thus cause the instability issue, current halide perovskite based solar cells with high PCEs exclusively contain the toxic element -Pb. This will inevitably cause potential environmental concerns for large-scale solar cell devices.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, inorganic cesium lead halides, CsPbX 3 (X=Cl, Br, I) show prominent compositional stability under thermal stress and remarkable photoelectric features with high electron mobility up to~1000 cm 2 V -1 s -1 [16]. In 2015, the first inorganic CsPbBr 3 perovskite solar cells (PSCs) were reported by Kulbak et al [17], acquiring a PCE of about 5%. More recently, Liao et al [18] reported CsPbX 3 nanowires stable solar cells with PCE of 1.21% and stability around 5500 h. Liang et al [19] reported carbon-based CsPbBr 3 solar cells with a PCE of 6.7% and stability over three months in humid air (90%-95% relative humidity, 25°C).…”
Section: Introductionmentioning
confidence: 99%
“…NPLs with thickness of only a few integer number of perovskite unit cells (1)(2)(3)(4)(5), present clear quantum size effects. We demonstrated emissions covering the entire visible spectrum and self-assembly of NPLs into higher order hierarchies.…”
mentioning
confidence: 99%